Role of Regulatory T Cells in Pathogenesis and Biological Therapy of Multiple Sclerosis - Milan Buc (Mediators of Inflammation)
Multiple sclerosis (MS) is an inflammatory disease in which the myelin sheaths around the axons of the brain and spinal cord are damaged, leading to demyelination and scarring as well as a broad spectrum of signs and symptoms. It is caused by an autoimmune response to self-antigens in a genetically susceptible individual induced by unknown environmental factors. Principal cells of the immune system that drive the immunopathological processes are T cells, especially of TH1 and TH17 subsets. However, in recent years, it was disclosed that regulatory T cells took part in, too. Subsequently, there was endeavour to develop ways how to re-establish their physiological functions. In this review, we describe known mechanisms of action, efficacy, and side-effects of contemporary and emerging MS immunotherapeutical agents on Treg cells and other cells of the immune system involved in the immunopathogenesis of the disease. Furthermore, we discuss how laboratory immunology can offer physicians its help in the diagnosis process and decisions what kind of biological therapy should be used.